Cost benefit analysis of three different urban bus drive systems using real driving data. (December 2015) - Gerbec, Marko; Samuel, Roman Oprešnik; Kontić, Davor
Graphical abstract: Highlights: Cost benefit analysis of city bus propulsion systems (diesel, hybrid, CNG). Ex-ante and Ex-post CBA results after three years of exploitation compared. Real-world driving exhaust emissions data used, including PM10 measurements. External costs from pollution (NO X, CO, CO2, PM10 and noise) assessed. CNG alternative most attractive in terms of economic and environmental incentives. Abstract: One of the CIVITAS-ELAN project measures in Ljubljana, Slovenia, was the introduction of alternative city bus propulsion systems (CNG, hydraulic hybrid buses) into the public transport and comparison of their performance in terms of costs and benefits with conventional (diesel) buses. A cost-benefit analysis was conducted to provide a model for identifying the most attractive alternative, with aim of aiding the decision making process for future rational up-scaling of the alternative propulsion technologies in PT fleet in Ljubljana. This paper focuses on presenting the key findings of this CBA, using real driving data, while demonstrating the sensitivity/variance of different parameters of a CBA, as well as the differentiation between uncertainties of parameters in an ex-ante analysis versus an ex-post analysis.